Guiding Value of Circulating Tumor Cells for Preoperative Transcatheter Arterial Embolization in Solitary Large Hepatocellular Carcinoma: A Single-Center Retrospective Clinical Study - Zhang, Qiao; Xia, Feng; Mo, Ali; He, Weiming; Chen, Jiazhen; Zhang, Weiqiao; Chen, Weiqiang (Frontiers in Oncology, 2022)
Background Large hepatocellular carcinoma (LHCC) is highly malignant and prone to recurrence, leading to a poor long-term prognosis for patients. There is an urgent need for measures to intervene in postoperative recurrence. Preoperative Transcatheter Arterial Embolization (TACE) is an effective treatment. However, there is a lack of reliable preoperative indicators to guide the application of preoperative TACE. We, therefore, investigated whether the preoperative status of circulating tumor cells (CTCs) could be used to guide preoperative TACE for HCC treatment. Methods This study recruited 361 HCC patients and compared recurrence-free survival (RFS) and overall survival (OS) in patients treated with TACE prior to surgery and those not treated with TACE. Patients were divided into CTC-positive group and CTC-negative group according to CTC status, and the effect of preoperative TACE on RFS and OS was compared in each subgroup. Results In CTC-positive patients, preoperative TACE reduces early recurrence and improves long-term survival. However, HCC patients did not benefit from preoperative TACE for the overall population and CTC-negative patients. Conclusions Preoperative CTC testing is a reliable indicator of whether HCC patients received TACE preoperatively. CTC positivity was associated with early tumor recurrence, and preoperative TACE could reduce early recurrence and long-term prognosis in CTC-positive patients.